Shear load transfer in high and low stress tendons. (May 2015) - Kondratko-Mittnacht, Jaclyn; Duenwald-Kuehl, Sarah; Lakes, Roderic; Vanderby, Ray
Abstract: Background: Tendon is an integral part of joint movement and stability, as it functions to transmit load from muscle to bone. It has an anisotropic, fibrous hierarchical structure that is generally loaded in the direction of its fibers/fascicles. Internal load distributions are altered when joint motion rotates an insertion site or when local damage disrupts fibers/fascicles, potentially causing inter-fiber (or inter-fascicular) shear. Tendons with different microstructures (helical versus linear) may redistribute loads differently. Method of approach: This study explored how shear redistributes axial loads in rat tail tendon (low stress tendons with linear microstructure) and porcine flexor tendon (high stress with helical microstructure) by creating lacerations on opposite sides of the tendon, ranging from about 20% to 60% of the tendon width, to create various magnitudes of shear. Differences in fascicular orientation were quantified using polarized light microscopy. Results and conclusions: Unexpectedly, both tendon types maintained about 20% of pre-laceration stress values after overlapping cuts of 60% of tendon width (no intact fibers end to end) suggesting that shear stress transfer can contribute more to overall tendon strength and stiffness than previously reported. All structural parameters for both tendon types decreased linearly with increasing laceration depth. The tail tendon had a more rapid decline in post-laceration elastic stress and modulus parameters as well as a more linear and less tightly packed fascicular structure, suggesting that positional tendons may be less well suited to redistribute loads via a shear mechanism. Graphical abstract: Highlights: High (flexor) and low (tail) stress tendons are pulled to create shear loading. High and low stress tendon structure and shear behavior are compared. Shear load transfer contributes to overall strength and stiffness of tendons. High stress tendon more effectively transfers shear than low stress tendon. High stress tendon has larger fascicular pitch angle than low stress tendon.